Experimental performance study on alkali-activated coal gangue-slag gel stabilized spoil for road base preparation - Xinyu Li; Jianan Sun; Yongjie Ding; Haoming Wang; Wei Wei (PLoS ONE, 2026)
This study developed a fully waste-based stabilized aggregate for road bases. A high-performance alkali-activated binder was synthesized from coal gangue and slag, then blended with tunnel-excavated spoil. Performance was compared to cement-stabilized spoil. The optimal mix had a slag-to-gangue ratio of 1:1, a sodium-silicate modulus of 0.8, a liquid-to-solid ratio of 0.38, and 14% alkali-activator content. Under this design, the binder reached 28-day compressive and flexural strengths of 46.2 MPa and 6.9 MPa, respectively. When used for spoil stabilization, the AA-GS system showed early-age strength benefits. UCS values reached 8–9 MPa across subbase dosages. Compared to cement-stabilized spoil, the AA-GS material reduced 90-day drying-shrinkage strain by 57.6%, water-loss rate by 23.4%, and shrinkage coefficient by 27.7%. The 28-day water-stability coefficient was no less than 0.876, and the freeze-thaw durability index remained at or above 0.80. These results demonstrate the AA-GS system offers strong mechanical performance and durability while enabling full reuse of tunnel spoil, coal gangue, and slag. The system was also designed with field applicability in mind, ensuring scalability and enabling real-world reuse of waste materials with tangible carbon reduction benefits.